KARAKTERISTIK BALITA PENDERITA PNEUMONIA RAWAT INAP DI RUMAH SAKIT UMUM DAERAH PARIAMAN SUMATERA BARAT TAHUN 2016 – FEBRUARI 2017 - Nadhiratul Syaputri; Rahayu Lubis; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Pneumonia is an infectious disease that is a major cause of death in children under five in the world. In 2016 Indonesia was the 7th highest in the world of mortality rate that caused by pneumonia.The case of pneumonia in West Sumatra on 2015 is 85% and Pariaman city is 39% which is the city with the third highest of pneumonia cases in the province of West Sumatra. The purpose of this study was to determine the characteristics of children under five hospitalized pneumonia patients in RSUD Pariaman West Sumatra. This research used case series design with the population is all ofchildren under five hospitalized pneumonia patients whose data was recorded in the medical records in RSUD Pariaman West Sumatra on 2016 - February 2017. The population were 108 patients and all were taken to be sampled. The data was collected from secondary data which is processed by univariate analyze by describing the variables and bivariate analyze using Chi-square test and Mann-Whittney test. Based on sociodemographic the highest proportion in the age group 0-11 months (38%), male (60.2%), Minangness (100%), Islam (100%), outside of Pariaman City (51.9%). The highest proportion found in children under five with good nutritional status (57.4%), incomplete basic immunization status (63%), with other diseases (82.4%), the average length of treatment for 6 days and return outpatient (54.6%). There is a significant difference of age based on immunization status (p=0,001), the average length of treatment based on the nutritional status (p=0,007) and other diseases suffered by (p=0,002). The result of this research are there is a significant difference of age based on immunization status, the average length of treatment based on the nutritional status and other diseases suffered by. Department of Health Promotion and Children's Ward in RSUD Pariaman to be more active in providing information about pneumonia to parents so they dont underestimate their child's illness, recognize the signs and symptoms of pneumonia and even prevent the occurrence of it. They also should be more active in providing information about the importance of complete basic immunization for children aged <1 year. Keywords : Children under five, Pneumonia of children under five, Patients characteristics